Neonatal herpes simplex virus infection combined with neonatal lupus erythematosus: a case reported - Jiang, Haiyan; Qiu, Hong; Wang, Minghuan; Yang, Haiyin; Li, Li; Li, Yanhong (Frontiers in Pediatrics, 2025)
BackgroundNeonatal herpes simplex virus (HSV) infection complicated by neonatal lupus erythematosus (NLE) is rare and is associated with high mortality and poor neurological outcomes in survivors. Enhancing clinical understanding of this condition is essential to reduce misdiagnosis and missed diagnosis.Case presentationA neonate presented with complete atrioventricular block (CAVB) as the initial clinical manifestation, which was successfully resolved following combined therapy with isoproterenol, hydrocortisone, and intravenous immunoglobulin (IVIG). Maternal history of HSV infection during pregnancy, coupled with suspected herpetic skin lesions in the neonate, strongly suggested HSV as the putative etiology. Despite initiation of acyclovir therapy for confirmed HSV infection, the recurrence of cutaneous rash prompted further evaluation, leading to the diagnosis of NLE. Notably, no specific treatment was administered for NLE, as the condition remained clinically quiescent. Follow-up at 7 months of age revealed no neurological abnormalities, no recurrence of CAVB, and gradual resolution of the rash.ConclusionThe clinical presentations of neonatal HSV infection and NLE can overlap. Early diagnosis and intervention are crucial for successful treatment and improved prognosis.